Perspectives of Business Personnel on Force Majeure as A Reason For Cutting Work Relationship in The Pandemic Time Covid -19 - Dordia Arinanda, Zsazsa (Journal of Private and Commercial Law, 2020)
The COVID-19 Pandemic outbreak that was experienced in almost all countries in the world, including Indonesia, added challenges as well as new anxiety for businesses and workers. The spread of COVID-19 in Indonesia increasingly adds to the difficulty of the national industrial sector. The COVID-19 pandemic can be categorized as a Force Majeure. It is a condition outside the wishes of the parties and cannot be predicted in advance, so the obligations specified in the contract cannot be fulfilled. Force Majeure can be used as a reason for companies to terminate their employees (PHK), as stipulated in "Article 164 paragraph (1) of Law No. 13 of 2003 concerning Labor", but companies must make every effort to protect the workers jointly. The practice that is happening right now is that many companies do layoffs without any protection for workers. The issue of how layoffs were under COVID-19 on the grounds of Force Majeure will be discussed in this study. The normative juridical method and the approach to legislation about labor were used in this research. The writer used secondary data such as primary legal materials, namely law, and literature related to research issues as secondary legal materials, collected through library studies, and analyzed descriptively analytically. The study result shows that layoffs on the grounds of Force Majeure due to the COVID-19 pandemic may be carried out by the company, but must still pay attention to workers' rights.